HUBUNGAN ANTARA UMUR DAN STATUS PERKAWINAN DENGAN KEJADIAN KANKER PAYUDARA DI INSTALASI BEDAH RUMAH SAKIT UMUM PUSAT DR. MOHAMMAD HOESIN PALEMBANG TAHUN 2012 - Rini Mayasari Rini Mayasari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2013)
ABSTRACT Breast cancer on the mark with the growth or uncontrolled growth of cells that are excessive. Factors affecting the incidence of breast cancer include maternal age, marital status, family history, hormone use, radiation, manarche, and obesity. The purpose of this study was to determine the relationship between Age and Marital Status of Mother with Breast Cancer incidence in the Installation Surgeon General Hospital Dr. Mohammad Hoesin Palembang in 2012. The study design was analytical descriptive with the approach in which the independent variables Cross Sectional Age Mother and Status Perkawianan and dependent variables in breast cancer incidence collected at the same time. The study population was all women who develop breast cancer in the Installation General Hospital Surgery Center Dr. Mohammad Hoesin Palembang in 2012 and samples taken by systematic random sampling with a sample of 130 respondents. The results of univariate analysis of data showed that respondents had breast cancer with a percentage of total 58 (44.61%) while respondents who had not had breast cancer totaled 72 by the percentage (63.39%). Respondents by Age Mothers who are at risk amounted to 34 by the percentage (26.15%) while respondents with Age Mothers who are not at risk amounted to 96 by the percentage (73.85%). Respondents by Marital Status is married and the mother who totaled 69 by the percentage (53.07%) and Marital Status with the status of unmarried women totaled 61 by the percentage (46.03%). Of Chi-Square test results found no significant relationship between Age Mothers with Breast Cancer event in which the p value = 0.007, no significant relationship between Marital Status in Breast Cancer event in which the p value = 0.030. Based on the results of the study, researchers suggest counseling efforts, medical knowledge and improve the quality of health services in order to reduce the incidence of breast cancer.. ABSTRAK Kanker payudara di tandai dengan pertumbuhan atau perkembangan tidak terkontrol dari sel-sel yang berlebihan. Faktor-faktor yang mempengaruhi kejadian kanker payudara antara lain umur ibu, status perkawinan, riwayat keluarga, penggunaan hormon, radiasi, manarche, dan obesitas. Tujuan penelitian ini adalah untuk mengetahui hubungan antara Umur Ibu dan Status Perkawinan dengan kejadian Kanker Payudara di Instalasi Bedah Rumah Sakit Umum Pusat Dr. Mohammad Hoesin Palembang Tahun 2012. Desain Penelitian ini adalah deskriptif analitik dengan pendekatan Cross Sectional dimana variabel independen Umur Ibu dan Status Perkawianan dan variabel dependen kejadian kanker payudara dikumpulkan dalam waktu yang bersamaan. Populasi penelitian ini adalah semua ibu yang menderita kanker payudara di Instalasi Bedah Rumah Sakit Umum Pusat Dr. Mohammad Hoesin Palembang Tahun 2012 dan sampel di ambil secara systematic random sampling dengan jumlah sampel 130 responden. Hasil analisis univariat data menunjukan responden yang mengalami Kanker Payudara berjumlah 58 dengan persentase sebesar (44,61%) sedangkan responden yang tidak mengalami Kanker Payudara berjumlah 72 dengan persentase (63,39%). Responden dengan Umur Ibu yang beresiko berjumlah 34 dengan persentase (26,15%) sedangkan responden dengan Umur Ibu yang tidak beresiko berjumlah 96 dengan persentase (73,85%). Responden dengan Status Perkawinan ibu yang berstatus kawin berjumlah 69 dengan persentase (53,07%) dan Status Perkawinan ibu yang berstatus tidak kawin berjumlah 61 dengan persentase (46,03%). Dari hasil uji Chi-Square didapatkan ada hubungan bermakna antara Umur Ibu dengan kejadian Kanker Payudara dimana p Value = 0,007, ada hubungan bermakna antara Status Perkawinan dengan kejadian Kanker Payudara dimana p Value = 0,030. Berdasarkan hasil penelitian, peneliti menyarankan upaya-upaya penyuluhan, pengetahuan tenaga medis dan meningkatkan mutu pelayanan kesehatan guna menurunkan angka kejadian kanker payudara.